Machiavelli and republicanism in Elizabethan England - Cerqueira, Marcone Costa (Griot : Revista de Filosofia, 2021)
The purpose of this succinct work is to present N. Machiavelli's classic republican view from his proposition of an inevitable paradox, the founding of an expansionist republic, difficult to govern, or the founding of a stable, but small and weak republic. Such a paradox, according to Machiavelli, should direct and condition all the constitutive devices of the republic when choosing what will be its destiny as a political body. The model of republic preferred by the Florentine will be the expansionist model of Rome, leading him to assume all the devices that gave this republic its power. From this presentation of the Machiavellian proposition, we will analyse the assimilation of republican thought in England from the Elizabethan period, as well as the political-social scenario that exists there. This itinerary will allow us to understand, in general, why classical republicanism was received on English soil from the perspective of establishing a mixed, stable government, thus favouring the spread of the Venice myth as a serene republic and delaying the use, even that mitigated, of the republican presuppositions expressed in the Machiavellian work that directed towards a Roman model.